2013
DOI: 10.1136/inp.f2868
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in dogs and cats 1. Pathogenesis and diagnosis

Abstract: Acute kidney injury (AKI), an abrupt loss of renal function, is a commonly encountered emergency in small animal practice. This article, the first of two on AKI, reviews the pathophysiology and diagnosis of the condition in dogs and cats. The second article, to be published in the June issue of In Practice, will cover the treatment, recovery and prognosis associated with AKI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 9 publications
0
24
0
6
Order By: Relevance
“…; Mugford et al. ). Four sequential stages of AKI have been identified: initiation, extension, maintenance and recovery (Devarajan ; Basile et al.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…; Mugford et al. ). Four sequential stages of AKI have been identified: initiation, extension, maintenance and recovery (Devarajan ; Basile et al.…”
Section: Introductionmentioning
confidence: 97%
“…; Mugford et al. ). Animal studies have shown that therapeutic interventions to reverse or prevent further progression of AKI must occur during the initiation or extension phases (Devarajan ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Once the diagnosis of AKI is established, any concurrent medications with nephrotoxic properties (see the first article in this series for more details [Mugford and others 2013]) should be discontinued immediately. In addition, specific therapies to eradicate any known or suspected causes of AKI should be implemented.…”
Section: Specific Therapiesmentioning
confidence: 99%
“…A injúria renal aguda (IRA) é uma doença multifatorial, extremamente frequente em unidades de terapia intensiva (UTI), que complica várias condições clínico-cirúrgicas, além de estar associada à elevada taxa de morbimortalidade (Costa et al 2003, Nunes et al 2010, Mehta et al 2011, Harison et al 2012, Mugford et al 2013. Entretanto, seus efeitos podem ser minimizados quando diagnosticada e [Cystatin C in critically ill dogs at UTI.]…”
Section: Introductionunclassified